Chlamydia trachomatis and Neisseria gonorrhoeae infection and the sexual behaviour of men who have sex with men. Issue 2 (4th October 2006) - Benn, P D; Rooney, G; Carder, C; Brown, M; Stevenson, S R; Copas, A; Robinson, A J; Ridgway, G L
Abstract : Background: : Rates of bacterial sexually transmitted infections (STIs) continue to rise among men who have sex with men (MSM) in the UK. Objective: To evaluate factors associated with Chlamydia trachomatis and Neisseria gonorrhoeae among MSM attending a genitourinary medicine clinic in inner London. Study design: : 599 MSM undergoing testing for STIs were recruited. Specimens for ligase chain reaction (LCR), strand displacement amplification (SDA) assay and culture were collected from the pharynx, urethra and rectum for the detection of C trachomatis and N gonorrhoeae . Details regarding demographics, symptoms, signs and sexual behaviour were recorded. Associations of these factors with each infection were tested, adjusting for other risk factors. Results: The prevalence of C trachomatis and N gonorrhoeae was 11.0% and 16.0%, respectively. LCR and SDA performed well for the detection of C trachomatis and N gonorrhoeae from urethra and rectum. Using either method, compared with our current testing policy, over 18% of those with C trachomatis and N gonorrhoeae would not have had their infection diagnosed or treated. Age, sexual behaviour, urethral and rectal symptoms and signs were strongly associated with both infections. A total of 33.7% of men reported at least one episode of unprotected anal intercourse in the previous month. Men reporting multiple episodes were markedly more likely to be HIV positive. Conclusion: The prevalence of infection, rates of partner acquisition and unprotected anal intercourse reported among these MSM are alarming. Improved detection of C trachomatis and N gonorrhoeae using nucleic acid amplification tests has major public health implications for STI and possibly HIV transmission in this population.